We went to the woods : a novel - Dolan-Leach, Caite (Random House, 2019)
Convinced that society is on the brink of collapse, five disillusioned twenty-somethings create a self-sustaining socialist commune, before their utopian vision is marred by desire, suspicion, and betrayal.